FAKTOR-FAKTOR YANG BERPERAN DALAM KELANGKAAN PUPUK BERSUBSIDI - Dita Lina Kuadrati; Ati Kusmiati (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2010)
The scarcity of subsidized fertilizer in subdistrict of Wonosari, Bondowoso Country affects the farmer’s exertion. Agriculture product decreases and to be hopeless. By this reason, farmers suffer operating loss. This will affect the available of national food. The scarcity of subsidized fertilizer in subdistrict of Wonosari, Bondowoso Country happened on the third of seasonal planting in 2007. This research is aimed to know: (1) Scarcity factors of subsidized fertilizer; (2) The effect of the scarcity of subsidized fertilizer on the farmer’s motivation in maintaining farmer exertion; and (3) The effect of the scarcity of subsidized fertilizer on the productivity of farmer’s exertion, especially on rice plant. This research is conducted conciously (Purposive Method). It is located in subdistrict Wonosari, Bondowoso Country. The research uses descriptive and comparative method. Sample was taken by using Cluster Sampling method consisting 35 respondents. On the other hand, the researcher also used Puposive Sampling method to determine the respondents criteria. Other respondents (beyond farmer) are the commision of subsidized fertilizer’s superintendant, field instructor, legitimated kiosk of subsidized fertilizer, and distributor of subsidized fertilizer. Method the data analysis used descriptive analysis through indicators and stage test analysis of Wilcoxon. The result of the research shows that: (1) Scarcity factors of subsidized fertilizer that is the dependence of farmer on inorganic fertilizer, imbalance of fertilizer and menimizing role recommended by the goverment, extensification of area, and informal distributor of subsidized fertilizer; (2) The farmer’s motivation is still high even the subsidized fertilizer is scarce; (3) The difference of productivity of farmer’s exertion, especially on the rice farming.Key Words: Scarcity of subsidized fertilizer, motivation, productivity exertion, and farmers